Morphological characteristic of capillary malformations of head and neck - I. V. Homolyako; S. P. Galych; O. A. Gyndych; I. P. Ogorodnyk (Zaporozhye State Medical University, 2014)
Aims. Study of morphological characteristics of capillary malformations of head and neck. Methods and results. Simply and combined capillary malformations of head and neck were defi ned into 3 groups according to pathohistological investigation of operation specimens. Groups had signifi cant structure differences: capillary, nodular capillary malformations, capillary-arteriovenous malformations. Pathohistological characteristics of each form were discussed. Conclusion. According to the results of the study the combined capillary-arteriovenous malformations cases are the most frequent. The cases of simple capillary malformations with the nodular formations are less frequent (2-nd place). The surgical tactics for the patients must be determined by the type of the malformation (simple capillary or combined forms).